2019
DOI: 10.1038/s41598-019-51604-z
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Quinoline Drugs Inhibit β-Hematin and Increase Free Hemin Catalyzing Peroxidative Reactions and Inhibition of Cysteine Proteases

Abstract: Malaria caused by Plasmodium affects millions people worldwide. Plasmodium consumes hemoglobin during its intraerythrocytic stage leaving toxic heme. Parasite detoxifies free heme through formation of hemozoin (β-hematin) pigment. Proteolysis of hemoglobin and formation of hemozoin are two main targets for antimalarial drugs. Quinoline antimarial drugs and analogs (β-carbolines or nitroindazoles) were studied as inhibitors of β-hematin formation. The most potent inhibitors were quinacrine, chloroquine, and amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 92 publications
1
48
0
Order By: Relevance
“…In the light of our evidence implicating PV5 in Hz formation, we next tested whether parasites with affected PV5 function display altered sensitivity toward chloroquine, a 4-aminoquinoline which is thought to inhibit heme biomineralization in Plasmodium ( 22 25 ). The absence of Pf PV5 did not detectably alter sensitivity toward chloroquine or any other tested antimalarial drug in cultured P. falciparum parasites ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the light of our evidence implicating PV5 in Hz formation, we next tested whether parasites with affected PV5 function display altered sensitivity toward chloroquine, a 4-aminoquinoline which is thought to inhibit heme biomineralization in Plasmodium ( 22 25 ). The absence of Pf PV5 did not detectably alter sensitivity toward chloroquine or any other tested antimalarial drug in cultured P. falciparum parasites ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The parasite’s dependency on heme detoxification has long been exploited in antimalarial therapy with outstanding success. Aminoquinolines inhibit Hz formation via direct physical interactions with hematin and the crystal surface, eventually leading to the build-up of cytotoxic free heme ( 22 25 ). The aminoquinoline chloroquine was the front-line medication against malaria from the 1950s onward until the emergence of widespread drug resistance restricted its utility ( 26 ).…”
mentioning
confidence: 99%
“…Proteases have been implicated in a wide range of malaria parasite metabolic processes including hemoglobin degradation; therefore, additional investigations were carried out in order to gain a better understanding of the actions of the test compound. Indeed, the antimalarial activity of quinoline-based antimalarials is attributed to their interference with hemoglobin metabolism either by inhibiting the uptake of hemoglobin by the parasite, or by inhibiting degradation of hemoglobin, or by binding the toxic hematin and preventing hemozoin formation, all of which result in the eventual death of the parasite [28][29][30] . In the present study, both ring and trophozoite stage parasites treated with (±)-moxiquindole were found to accumulate hemoglobin to a greater extent than parasites treated with either chloroquine or artemisinin (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Other experimentally identified CQ/HCQ targets include phospholipase A2 ( 56 59 ), porphyrins ( 60 , 61 ), and even DNA at high CQ concentrations around 1 mM ( 42 ) ( Table 2 ).…”
Section: General Mechanisms Of Cq/hcq Actionsmentioning
confidence: 99%